The Determinants Of Occupational Stress In Malaysia Organization - Keong, Kooi Eng (2009)
The main objective of this study is to determine the generic factors that influence the occupational stress of employees in Malaysia organizations. The secondary objective is to use the findings to recommend ways to minimize occupational stress in the organizations.